Damage Constitutive Model of Microcrack Rock under Tension - Huiya Niu; Xingyu Zhang; Zhigang Tao; Manchao He (Advances in Civil Engineering)
To investigate the tensile properties of brittle rock with microdamage, an indirect tensile test was conducted. High-speed image acquisition and acoustic emission (AE) were applied to record the process. After the tests, the images were analysed using the digital image correlation (DIC) method to obtain the stress and strain development of the rock under tension. The damage constitutive model was also developed in this study. Based on known and assumed statistical distributions for microcracks and the theory of fracture and statistical damage, the mechanical properties and failure mechanisms of brittle rock under tension were analysed. The basic statistical parameters of the main cracks in the elements were described, and the damage variable was defined to develop the effective modulus. A constitutive model for microdamage brittle rock-like materials was established based on the effective modulus. Additionally, to describe the crack propagation, a random-direction crack under tension was analysed to calculate the crack-tip stress intensity factor. After applying the basic parameters of the sandstone to the analytical model, the results showed that the analytical model agreed with the experimental results.